2016
DOI: 10.1016/j.jad.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of DSM-IV-TR major depressive disorder, self-reported diagnosed depression and current depressive symptoms among adults in Germany

Abstract: Background: While standardized diagnostic interviews using established criteria are the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
68
1
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 59 publications
12
68
1
5
Order By: Relevance
“…Our results support many previous findings indicating that low objective SES is associated with depressive symptoms and depressive disorders [57, 64]. The findings also accord with those of earlier studies suggesting that income is more strongly associated with depressive symptoms than is education.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results support many previous findings indicating that low objective SES is associated with depressive symptoms and depressive disorders [57, 64]. The findings also accord with those of earlier studies suggesting that income is more strongly associated with depressive symptoms than is education.…”
Section: Discussionsupporting
confidence: 93%
“…Many people who are positively screened on this measure may have subthreshold depressive symptoms [7]. Other limitations arise from the relatively low response rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many large-scale health surveys, the prevalence of depression is assessed by asking participants whether they have been diagnosed with depression by a health professional in the past 12 months [14]. This simple measure has various preconditions such as previous health care utilization of the respondent, reporting depressive symptoms to a health professional, understanding the question asked in the survey, and admitting the diagnosis in the survey interview.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these preconditions, a recent general population survey found that 12-month prevalence estimates based on the respondent’s report of a clinician-diagnosis of depression and an interviewer assessment of major depression with a comprehensive standardized diagnostic interview based on the Diagnostic and Statistical Manual of Mental Disorders-IV (DSM-IV) were on a similar level [1]. Yet, the overlap of the two measures was only moderate, and, in agreement with previous research [2, 4, 9, 10], prevalence of major depression was highest in younger age adults and of clinician-diagnosed depression in middle-aged and older adults [1].…”
Section: Introductionmentioning
confidence: 99%